2017
DOI: 10.3390/ijms18112479
|View full text |Cite
|
Sign up to set email alerts
|

Ergostane-Type Sterols from King Trumpet Mushroom (Pleurotus eryngii) and Their Inhibitory Effects on Aromatase

Abstract: Two new ergostane-type sterols; (22E)-5α,6α-epoxyergosta-8,14,22-triene-3β,7β-diol (1) and 5α,6α-epoxyergost-8(14)-ene-3β,7α-diol (2) were isolated from the fruiting bodies of king trumpet mushroom (Pleurotus eryngii), along with eight known compounds (3–10). All isolated compounds were evaluated for their inhibitory effects on aromatase. Among them, 4 and 6 exhibited comparable aromatase inhibitory activities to aminoglutethimide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Some examples are polysaccharides, glycoproteins, proteoglycans, proteins, quinones, cerebrosides, isoflavones, catechols, triacylglycerols, phenolic acids, terpenes, and steroids (Ferreira et al, 2010;Villares et al, 2012). Evidences support the theory of antitumoral properties of sterols, including inhibition of tumor growth and stimulation of apoptosis (Kikuchi et al, 2017). According to Barreira and Ferreira (2015), the mechanism underlying the inhibition of cell growth could be similar to the mechanism associated with protein kinase C activity.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are polysaccharides, glycoproteins, proteoglycans, proteins, quinones, cerebrosides, isoflavones, catechols, triacylglycerols, phenolic acids, terpenes, and steroids (Ferreira et al, 2010;Villares et al, 2012). Evidences support the theory of antitumoral properties of sterols, including inhibition of tumor growth and stimulation of apoptosis (Kikuchi et al, 2017). According to Barreira and Ferreira (2015), the mechanism underlying the inhibition of cell growth could be similar to the mechanism associated with protein kinase C activity.…”
Section: Introductionmentioning
confidence: 99%
“…The ergosterol content in P. eryngii was reported as 20 mg/100 g dw, although a higher value was measured in commercial samples (Souilem et al 2017). Kikuchi et al (2017Kikuchi et al ( , 2018 reported the isolation and structure elucidation of ergostane type sterols and bisabolane-type sesquiterpenes from P. eryngii with aromatase and nitric oxide production inhibitory effects, respectively (Table 2). Wang et al (2013a) reported the identification of novel and rare perhydrobenzannulated 5,5-spiroketal sesquiterpenes, named pleurospiroketals A-E from the edible mushroom P. cornucopiae with inhibitory activity against nitric oxide production in lipopolysaccharide-activated macrophages with IC 50 values between 6.8-20.8 lM.…”
Section: Triterpenoids and Sterolsmentioning
confidence: 99%
“…Many sterols such as campesterol, lanosterol, brassicasterol, b-sitosterol, ergosterol were analyzed in the fruiting bodies of different Tuber species Pleurotus ostreatus Ergosterol, ergosta-5,7-dienol, ergosta-7-enol, ergosta-7,22-dienol, oleanolic acid, ursolic acid Sarma et al (2018) and Koutrotsios et al (2017) Pleurotus eryngii Ergosterol Souilem et al (2017) Ergostane-type sterols Kikuchi et al (2017) Strophasterols E and F Kikuchi et al (2019) ( Table 2). The main sterols found in Tuber magnatum Picco and T. melanosporum fruiting bodies were ergosterol and brassicasterol, which amounted to 63.1-66.7% and 15.7-21.3% of the total sterols, respectively.…”
Section: Triterpenoids and Sterolsmentioning
confidence: 99%
“…Many studies have shown that mushrooms have different biological activities. In studies on mushrooms, it has been reported to have many activities such as antioxidant, antitumor, antimicrobial, antiaromatase activity, anti-inflammatory activity, antiproliferative activity and immunomodulatory activity (Akgul et al, 2017;Bal et al, 2017;Kikuchi et al, 2017;Sriramulu and Sumathi, 2017;Wang et al, 2018;Sevindik 2018a;Gürgen et al, 2020;Mushtaq et al, 2020). Turkey has a high diversity in terms of biodiversity.…”
Section: Introductionmentioning
confidence: 99%